2021
DOI: 10.3390/ijms22094472
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Viral Entry Proteins in Hyperandrogenemic Female Mice: Implications for Women with PCOS and COVID-19

Abstract: SARS-CoV-2, the causative agent of COVID-19, infects host cells using the angiotensin I converting enzyme 2 (ACE2) as its receptor after priming by host proteases, including TMPRSS2. COVID-19 affects multiple organ systems, and male patients suffer increased severity and mortality. Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder in reproductive-age women and is characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. PCOS is associated with obesity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…In addition, Panx-1 blockers also reduce the secretion of proteases into the extracellular space, such as cathepsins (Swayne et al, 2020). Extracellular proteases, such as furin and cathepsins, promote SARS-CoV-2 infection over other coronaviruses, as demonstrated by others (Bestle et al, 2020;Dessie and Malik, 2021;Huffman et al, 2021;Murgolo et al, 2021;Raghav et al, 2021;Rossi et al, 2020;Watzky et al, 2021;Zhang et al, 2021), and our current data support these findings by identifying a novel mechanism of virus-mediated inflammation. Our data that ATP, PGE 2 , and IL1b are highly concentrated in the BAL obtained from COVID-19 individuals is exciting but needs to be considered carefully due to the fact that during the evolution of the disease, significant apoptosis of lung cells occurs (Liu et al, 2021).…”
Section: Analysis Of Bronchiolar Alveolar Lavage From Covid-19 Individuals Confirms the Accumulation Of Atp Pge 2 And Il1bsupporting
confidence: 85%
“…In addition, Panx-1 blockers also reduce the secretion of proteases into the extracellular space, such as cathepsins (Swayne et al, 2020). Extracellular proteases, such as furin and cathepsins, promote SARS-CoV-2 infection over other coronaviruses, as demonstrated by others (Bestle et al, 2020;Dessie and Malik, 2021;Huffman et al, 2021;Murgolo et al, 2021;Raghav et al, 2021;Rossi et al, 2020;Watzky et al, 2021;Zhang et al, 2021), and our current data support these findings by identifying a novel mechanism of virus-mediated inflammation. Our data that ATP, PGE 2 , and IL1b are highly concentrated in the BAL obtained from COVID-19 individuals is exciting but needs to be considered carefully due to the fact that during the evolution of the disease, significant apoptosis of lung cells occurs (Liu et al, 2021).…”
Section: Analysis Of Bronchiolar Alveolar Lavage From Covid-19 Individuals Confirms the Accumulation Of Atp Pge 2 And Il1bsupporting
confidence: 85%
“…Total kidney and LV RNA were extracted, DNAse treated, quantified, and reverse transcribed (5 µg), as previously described [ 37 , 99 ]. Quantitative RT-PCR was performed using TaqMan gene expression assays (Applied Biosystems, Foster City, CA, USA) for Ace2 (Mm01159006_m1), Tmprss2 (Mm00443687_m1), Tmprss4 (Mm00520486_m1), Furin (Mm00440646_m1), Ctsl (Mm00515597_m1), Adam17 (Mm00456428_m1), Gapdh (Mm99999915_g1), B2m (Mm00437762_m1), Actb (Mm02619580_g1), and 18S rRNA (Hs99999901_s1).…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that excess androgens in a rodent model of PCOS upregulate ACE2 protein expression in the heart, kidney, and small intestine [ 37 ]. Whether obesity, a comorbidity of both PCOS and COVID-19, modulates SARS-CoV-2 viral entry factors in cardiovascular and renal systems in PCOS is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As previously stated, androgens favor SARS-CoV-2 infection [ 52 , 56 58 , 126 – 130 ]. Studies of these phenomena in humans are supported by animal models [ 123 ]. In addition to higher susceptibility to the SARS-CoV-2 virus, women with hyperandrogenic PCOS phenotype have more pronounced symptoms than women with PCOS and normal androgen levels [ 131 ].…”
Section: Covid-19 and Pcosmentioning
confidence: 99%
“…In PCOS, elevated androgens upregulate the SARS-CoV-2 receptor ACE2 and modify host proteases to increase SARS-CoV-2 viral entry into tissues. The Up arrow signifies increase(s); the lightning bolt represents injury (from Lizneva et al [ 122 , 123 ], with permission of CC-Creative Commons License Deed) …”
Section: Covid-19 and Pcosmentioning
confidence: 99%